2013
DOI: 10.1093/jnci/djs629
|View full text |Cite
|
Sign up to set email alerts
|

Combining Radiotherapy and Cancer Immunotherapy: A Paradigm Shift

Abstract: The therapeutic application of ionizing radiation has been largely based on its cytocidal power combined with the ability to selectively target tumors. Radiotherapy effects on survival of cancer patients are generally interpreted as the consequence of improved local control of the tumor, directly decreasing systemic spread. Experimental data from multiple cancer models have provided sufficient evidence to propose a paradigm shift, whereby some of the effects of ionizing radiation are recognized as contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
719
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 890 publications
(731 citation statements)
references
References 117 publications
7
719
0
5
Order By: Relevance
“…Antibodies that block negative immune regulatory pathways (checkpoint inhibitors) 5 , including CTLA-4 (cytotoxic T-lymphocyte–associated antigen 4) and PD-1 (programmed cell death 1) receptors, improve survival in patients with advanced disease such as melanoma, bladder, squamous cell head and neck and non-small-cell lung cancer 611 . A key clinical approach to improving cancer immunotherapy has been to combine radiotherapy with checkpoint inhibitors to induce the abscopal effect, a phenomenon where local tumor treatment produces systemic regression of metastatic lesions 12 . The abscopal effect is facilitated by the immune system and has been found anecdotally to mediate long-term, durable clinical responses.…”
mentioning
confidence: 99%
“…Antibodies that block negative immune regulatory pathways (checkpoint inhibitors) 5 , including CTLA-4 (cytotoxic T-lymphocyte–associated antigen 4) and PD-1 (programmed cell death 1) receptors, improve survival in patients with advanced disease such as melanoma, bladder, squamous cell head and neck and non-small-cell lung cancer 611 . A key clinical approach to improving cancer immunotherapy has been to combine radiotherapy with checkpoint inhibitors to induce the abscopal effect, a phenomenon where local tumor treatment produces systemic regression of metastatic lesions 12 . The abscopal effect is facilitated by the immune system and has been found anecdotally to mediate long-term, durable clinical responses.…”
mentioning
confidence: 99%
“…Although SBRT has shown its superior effect on OS in the early stage of NSCLC patients compared with conventional-dose and fractionated radiotherapy, 83 tumor relapse and disease progression often occurred after ionizing irradiation. Apart from direct necrotic death of tumor cells caused by high-intense radiation, radiotherapy has crosstalk with the immune system, indeed, 84 presenting as: (1) induces immunogenic cell death to recruit antitumor T cells to the irradiated site 85,86 ; (2) upregulates expression of MHC I, which were previously downregulated for immune escape 87 ; and (3) expand the diversity of the T cell receptor (TCR) repertoire to detect varieties of tumor antigens. 88 Taken together, radiotherapy is an ingenious modality to convert tumor cells in situ vaccine and this provides a rationale for combing radiotherapy with immunotherapy.…”
Section: Combined With Radiotherapymentioning
confidence: 99%
“…Clinically, it has been shown that concurrent CRT regimens significantly improve 5-year survival compared with sequential CRT (8,9), and ICD may be responsible for these improved treatment outcomes (40). Ionizing radiation (15,16) and some types of chemotherapy, such as oxaliplatin and anthracyclines (13), are known to induce ICD. Using an in vitro model, Golden and colleagues (41) recently showed that ionizing radiation dose-dependently induced ICD, and when combined with carboplatin or paclitaxel, radiation treatment enhanced the ICD effect.…”
Section: Discussionmentioning
confidence: 99%
“…Administering chemotherapy and RTX concurrently may also result in immunogenic cell death (12)(13)(14), which has implications for the use of immunotherapy in combination with CRT. Ionizing radiation (15,16) and some types of chemotherapy, such as anthracyclines and oxaliplatin (13), are known to induce immunogenic cell death, whereas other therapies may result in tolerogenic cell death (17). Although cisplatin by itself is not known to produce immunogenic cell death (18), it is commonly combined with RTX, which is a powerful inducer of calreticulin exposure (16), leading to the induction of immunogenic cell death (18).…”
Section: Introductionmentioning
confidence: 99%